Laws of City Hall Kuala Lumpur : with cases and commentaries / A. Gnanarajah - Gnanarajah, A. , 1936- (International Law Book Services, 1992)
Compilation of all the Acts of Parliament, by-laws, regulations, orders, notifications, appointments, delegations, and declarations that are enforced by the City Hall Kuala Lumpur.